The Effect of Change Management on Madrasah Aliyah and Tsanawiyah at Darul Muta'allimin Islamic Boarding School Tanah Merah, Aceh Singkil - Raudatun Sumi; Nuri Aslami (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
This study aims to determine the extent of the development of corporate management in a Madrasah Pondok Pesantren in Aceh Singkil and to find out how the management system is used and what changes have occurred. The type of research used is a qualitative approach. The research method is in the form of literature study, then with analysis and stages. This change management can help an organization or company develop knowledge that has never been practiced in an organization, of course this change management does not have to be done spontaneously but slowly or gradually by asking the opinions of members or work teams first and then presenting the intent and the purpose of the changes designed so as not to cause debate and mutual acceptance.